Technological Innovation, Investment in Research and Development, Human Capital and Their Impact on Economic Growth (Journal of Asian Development Studies, 2026)
The aim of this study is to investigate the impact of technological innovation, research and development investment, and human capital on economic growth using 25-year time-series data from 2000 to 2024, sourced from the World Bank’s World Development Indicators. The study employed various econometric techniques; descriptive statistics were used to report the mean, median, and mode, as well as the Jarque-Bera test values and the data's skewness. The unit root test (Augmented-Dickey Fuller) was used to test the stationarity of the values of selected variables. Some values were stationary at a level, while others were stationary on first differences. The ARDL (Auto-Regressive Distributed Lag) model was selected as the most suitable method for this study. Variance Inflation Factor, Heteroscedasticity test, and Ramsay RESET were used to identify multicollinearity, heteroscedasticity, and issues with the model's variable specification. The findings from ARDL and Error Correction Models reveal a positive and significant association between technological innovation, investment in R&D, human capital, and economic growth. The study suggests that policymakers must focus on technological innovation, increase investment in R&D, and build human capital to accelerate economic growth. These results can be generalised to other developing countries facing similar issues of low technological innovation, low investment in R&D, underdeveloped human capital, and stagnant economic growth.